A study of whiplash injury occurrence mechanisms using human head-neck finite element model (Analysis of factors for reproducing the early head-neck behaviors in rear impact) - Junji HASEGAWA; Hiromichi NAKADATE; Shigeru AOMURA (Nihon Kikai Gakkai ronbunshu, 2018)
The number of whiplash injuries worldwide is at a high level. From the mid-1990s, many researchers have focused into the head-neck S-shaped mode deformation behavior in early rear impacts. Firstly we developed a Japanese male 50th%ile size head-neck FE model, so we attempt to reproduce the same mode in head-neck behaviors in the rear impact sled tests of male subjects. This model has not only the main ligament tissues, but also nearly 40 major muscles such as the sternocleidomastoid muscle, the hyoid muscles, and the erector spinae muscles. Using DOE (Design of Experiments), we analyzed the percent contribution of neck muscles in the relaxed state under 1G, when holding the head neutral posture before rear impact and the muscle force balance was obtained based on the regression equation. Then, we carried out the rear impact simulation using same muscle strength, the results were compared with the head-neck behaviors of male subjects in rear sled impact tests. By balancing the muscular strength before the impact, it found out that the S-shaped mode deformation could be reproduced. This mode is strongly influenced by the muscle force balance, it has little influence on the head maximum rotational angle which occurred in the late rear impact. On the contrary, the muscular strength-up, which is reflexed on muscles such as sternocleidomastoid muscle and hyoid muscle after the impact, has little influence on the S-mode. We introduced an index (S - θmax) to quantify the S - shaped mode deformation, and confirmed that there is a possible correlation between the index value and the muscle strength for holding the head posture. Finally, we investigated the relationship between individual T1 conditions and S - θmax, so we also report these results.